PENGGUNAAN RUANG OLEH PELAKU USAHA BERBASIS RUMAH TANGGA (HBE) DI KECAMATAN SEMARANG TIMUR - Simbolon, Hotnida Yusnani (Jurnal Tataloka, 2009)
The result of this research shows that household enterprise and activity as well as the production process which becomethe reason to have a home industry influence the spatial use by household-based enterprisers. It is seen from their productionprocesses which utilize the streets in different locations because the insufficient space in their houses. This research finds out only 8%of the enterprisers add additional rooms. Besides, there is only 85% of the enterprisers fulfill the requirement of wide standart forperson, that is 9 mÂ². However, the overall width the enterprisers have is insufficient because the width of the building is equal withland width. This will be hard for household-based enterprises to implement the simple house criteria, that are houses as shelter andspace for business, because each household-based enterprise has different characteristic. Therefore, the relevance analysis shows thatr-value of income and spatial use is -0,015 to 0,453.The r value shows the low relevance and that income does not influence thespatial use by the enterprisers. This is propted by the fact that they do not have any willingness to add more rooms. They have alreadysatisfied by the space they have at home, no more land can be built, and that the enterprisers do not have more saving, sinceroom addition needs more money